Pengaruh Tekanan Internal Dan Eksternal Terhadap Kecurangan Laporan Keuangan Pada Bank Umum Indonesia Yang Terdaftar Di Bursa Efek Indonesia Periode 2015 - 2019 - Ananda Tiara, (2021)
The main objective of this study is to analyze the influence of internal and external pressures as proxied by variables of financial stability, insider ownership, debt and banking anti-fraud strategy on financial statement fraud. This study also using the firm size as a control variable. This study uses the F-Score Model to measure the potential for fraudulent financial statements. The sample used in this study were 105 samples consisting of 21 banking companies listed on the Indonesia Stock Exchange in 2015-2019. The data used is secondary data. The data analysis technique is panel data regression analysis which is processed by STATA v.16. The results of this study state that the debt variable has a significant negative influence on financial statement fraud. Meanwhile, other variables such as financial stability, insider ownership, banking anti-fraud strategy, and firm size have no influences on financial statement fraud.